Daughters of the country National Film Board of Canada. - National Film Board of Canada ([Montreal] NFBC, 1986)
A docu-drama on the marriage of two ladies, Ikwe and Madeline, who belong to a cultural minority group. It shows how their marriages failed because of culture and traditions.
1. Ikwe -- 2. Mistress Madeleine.
VHS.
Keywords: Interracial marriage -- Canada; Sociology